Peran Profitability dalam Memoderasi Pengaruh Predictor Debt Policy - Law, Jimmy; Akilah; Shane, Cindy; Firza, Syafira Ulya; Sigalingging, Eni Duwita (Owner : Riset dan Jurnal Akuntansi, 2024)
The research aims to examine and analyze the effect of business risk, company growth, company size, asset structure, and free cash flow on debt policy with profitability as a moderating variable. The population of this study consists of 191 mining companies for the period of 2020-2022 listed on Indonesia Stock Exchange (IDX). The sampling technique was purposive sampling and 106 company were used. This type of research was correlational method. Data analysis was performed using classical assumption, hypothesis testing, and moderating regression (MRA) using IBM SPSS 25 version. Partially, the result of the study indicate that company growth and company size had a significant positive effect on debt policy; free cash flow had a significant negative effect on debt policy; meanwhile, business risk and asset structure had no significant effect on debt policy. The result of the moderation test in this study indicate that profitabiliy can moderate the effect of company growth on debt policy. Meanwhile, profitability is unable to moderate the effect of business risk, company size, asset structure, and free cash flow on debt policy.